2021
DOI: 10.1098/rstb.2020.0333
|View full text |Cite
|
Sign up to set email alerts
|

Cross-frequency coupling explains the preference for simple ratios in rhythmic behaviour and the relative stability across non-synchronous patterns

Abstract: Rhythms are important for understanding coordinated behaviours in ecological systems. The repetitive nature of rhythms affords prediction, planning of movements and coordination of processes within and between individuals. A major challenge is to understand complex forms of coordination when they differ from complete synchronization. By expressing phase as ratio of a cycle, we adapted levels of the Farey tree as a metric of complexity mapped to the range between in-phase and anti-phase synchronization. In a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…In many fields, techniques for quantifying the synchrony of signals have historically been crude, but have recently become more detailed, thereby enhancing progress. For instance, one paper in this special issue develops newly detailed frequency-specific descriptions of a kind of synchrony, and then uses them to make new inferences about musical and rhythmic behaviour in humans [37]. The examples of [38] on the interactive vocalizations of primates are also enhanced by a frequency-specific perspective: fig.…”
Section: Resultsmentioning
confidence: 99%
“…In many fields, techniques for quantifying the synchrony of signals have historically been crude, but have recently become more detailed, thereby enhancing progress. For instance, one paper in this special issue develops newly detailed frequency-specific descriptions of a kind of synchrony, and then uses them to make new inferences about musical and rhythmic behaviour in humans [37]. The examples of [38] on the interactive vocalizations of primates are also enhanced by a frequency-specific perspective: fig.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers are increasingly foregoing ultimate control for a more ecologically valid approach that enables participants to have more powerful aesthetic experiences. This study follows others that have moved more into the ‘wild’ to explore such naturalistic experiences (Chabin et al, 2022; Czepiel et al, 2021; Dotov & Trainor, 2021; Merrill et al, 2021; Swarbrick et al, 2019; Tervaniemi et al, 2021). The current findings show that self-reported aesthetic experience significantly increases in audiovisual (compared to audio only) piano performances in the naturalistic setting of a concert hall.…”
Section: Discussionmentioning
confidence: 97%
“…Focusing more specifically on the role of modality, to date only a few studies compare responses to AV vs. AO conditions in naturalistic settings. Compared to eyes-closed conditions, eyes-open conditions increased movement energy and interpersonal coordination, suggesting that visual information may enhance the social aspect of live pop/soul music (Dotov & Trainor, 2021). Coutinho & Scherer (2017) compared emotional responses in a live AV performance to recorded AV, AO, and VO performances of Schubert Lieder, where the live AV condition had significantly higher wonder and significantly lower boredom ratings.…”
Section: Introductionmentioning
confidence: 99%
“…If not, what could account for their absence? Dotov & Trainor [17] recognized this curious problem and approached it experimentally as well as via modelling. The classic 'finger tapping test' showed that human subjects were unable to sustain other phase relationships, e.g.…”
Section: Cognitive Mechanismsmentioning
confidence: 99%